"Cross-linked fibrous" spherulites formed from a low molecular weight compound, Fmoc-functionalized phenolic amino acid1. Issue 21 (7th June 2015) - Reddy, Samala Murali Mohan; Shanmugam, Ganesh; Mandal, Asit Baran
<x xml:space="preserve">Abstract</x> Spherulites with highly "cross-linked microfibrils" are identified from a simple, low molecular weight compound such as Fmoc-L-tyrosine, using supramolecular self-assembly process.